Pengaruh Personal Financial Needs dan Financial Stability terhadap Kecurangan Laporan Keuangan - Nabila Aisha Fatharani; Pupung Purnamasari (UNISBA Press, 2023)
Abstract. Personal financial needs and financial stability become a pressure factor that encourages individuals or groups to commit financial statement fraud. This study aims to determine how much influence personal financial needs and financial stability have on fraudulent financial statement. The method used in this study is a descriptive method with a quantitative approach. Source of data used in this research is secondary data. The population in this study were 26 companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period with a purposive sampling technique. Based on the result and conclusions of the study, it shows that personal financial needs as a proxy for the percentage of share ownership by insiders (OSHIP) and financial stability as a proxy for the percentage change in total assets (ACHANGE) each have a significant positive effect on fraudulent financial reporting. Abstrak. Personal financial needs dan financial stability menjadi suatu faktor tekanan yang mendorong individu atau kelompok untuk melakukan kecurangan pada laporan keuangan. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh personal financial needs dan financial stability terhadap kecurangan laporan keuangan. Metode yang digunakan dalam penelitian ini merupakan metode deskriptif dengan pendekatan kuantitatif. Sumber data yang digunakan dalam penelitian ini adalah data sekunder. Adapun populasi dalam penelitian ini sebanyak 26 perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2021 dengan teknik pengambilan sampel menggunakan purposive sampling. Berdasarkan hasil dan simpulan penelitian menunjukan bahwa personal financial needs dengan proksi presentase kepemilikan saham oleh orang dalam (OSHIP) dan financial stability dengan proksi presentase perubahan total aset (ACHANGE) masing-masing berpengaruh positif secara signifikan terhadap kecurangan laporan keuangan.